Clinical characteristics of the patients with Hodgkin's lymphoma involving extranodal sites - Li, Zhi-Ming (Sun Yat-sen University Cancer Center, 2012)
Differences between Hodgkin's lymphoma (HL) patients in China and Western countries are known to exist, but data on Chinese patients with HL are limited. It is not clear whether there are clinical and histological differences in patients with HL involving different extranodal sites. This is the first study to analyze Chinese patients with HL involving different extranodal sites. We selected 22 HL patients with extranodal involvement from more than 250 previously untreated HL patients. Most patients were young males, and 20 of the 22 patients had stage IV disease. The major pathologic types were nodular sclerosis classical HL (NSCHL) and mixed cellularity classical HL (MCCHL). At diagnosis, the most commonly involved extranodal sites were the liver and lung, followed by the bones. There was no significant association between the international prognostic score (IPS) and survival in patients with different extranodal sites. Our data showed the overall survival (OS) and disease-free survival (DFS) rates of low-risk group (IPS = 0-2) were relatively higher than those of high-risk group (IPS ≥ 3), but the IPS did not show predictive power for survival. Although HL with extranodal involvement is rare, it should be considered as a unique form of HL.